2020
DOI: 10.1155/2020/2892734
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Efficacy of Xpert CT/NG for Chlamydia trachomatis and Neisseria gonorrhoeae

Abstract: Background. Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) are widely spread across the world. Asymptomatic or inconspicuous CT/NG infections are difficult to diagnose and treat. Traditional methods have the disadvantages of low detection rate, inaccurate results, and long detection time. However, Xpert CT/NG makes up for the aforementioned shortcomings and has research value and popularization significance. Methods. PubMed, Embase, Cochrane Library, and Web of Science were systematically searched, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…For NG infection, the sensitivity and the specificity for the urine samples and cervical swabs were both higher than 99.0%. These results were comparable to those of previous evaluation studies ( Gaydos et al., 2013 ; Herbst-de-Cortina et al., 2016 ; Bristow et al., 2019 ; Xie et al., 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…For NG infection, the sensitivity and the specificity for the urine samples and cervical swabs were both higher than 99.0%. These results were comparable to those of previous evaluation studies ( Gaydos et al., 2013 ; Herbst-de-Cortina et al., 2016 ; Bristow et al., 2019 ; Xie et al., 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“… 18 Studies have reported greater than 98% sensitivity and over 99% specificity for detection of N gonorrhoeae in urine and vaginal swab specimens compared with other nucleic acid amplification tests. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…It is run on a platform of a two, four, or sixteen-module machine, requires an uninterrupted power supply and has an analytic time of ninety minutes. A meta-analysis of studies testing urine, vaginal, endocervical, anorectal, and pharyngeal samples for CT/NG revealed pooled sensitivities and specificities of 94 and 99% for CT, respectively, and 95 and 100% for NG, respectively [20]. Importantly, due to its role in tuberculosis diagnostics, the GeneXpert platform is widely available in many resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%